(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2007)
Maternal death audit is becoming a routine process in the practice of obstetric care in both developed and developing countries. Review of case records of maternal deaths between September 1999 and December 2004 was done to find out the profile of the patients and factors associated with the deaths in a periurban hospital in Dhaka. A total 40 maternal deaths occured among 14,137 live births amounting MMR 282 per 100,000 live births. Mean age of deceased mothers was 24.85± 5.6 years, 25% were primipara and vaginal delivery occurred in 42.46% cases. Thirty percent deaths occured within six hours of admission to hospital and 73% deaths occurred during post-partum period. The primary obstetric cause of deaths were severe pre-eclampsia and eclampsia (42.5%), haemorrhage (17.5%), obstructed labour (12.5%) and sepsis (7.5%) respectively. Facility based audit into maternal deaths provide an opportunity to understand the inciting factors and is recommended to be implemented for improvement of professional practice and management. (J Bangladesh Coll Phys Surg 2006; 24: 5-9)